2022
DOI: 10.3389/fimmu.2022.866087
|View full text |Cite
|
Sign up to set email alerts
|

Aminoacyl-tRNA Synthetases: On Anti-Synthetase Syndrome and Beyond

Abstract: Anti-synthetase syndrome (ASSD) is an autoimmune disease characterized by the presence of autoantibodies targeting one of several aminoacyl t-RNA synthetases (aaRSs) along with clinical features including interstitial lung disease, myositis, Raynaud’s phenomenon, arthritis, mechanic’s hands, and fever. The family of aaRSs consists of highly conserved cytoplasmic and mitochondrial enzymes, one for each amino acid, which are essential for the RNA translation machinery and protein synthesis. Along with their main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 191 publications
1
31
0
1
Order By: Relevance
“…Therefore, we could not individually evaluate the characteristics of anti-ARS antibodies, although anti-PL-7 and anti-PL-12 antibody positivity has been reported to be associated with severe ILD. 22 In summary, SPNM occurred more frequently in anti-MDA5 antibody-positive DM/PM patients than in anti-MDA5 antibody-negative DM/PM patients, and twothirds of the SPNM group were anti-MDA5 antibody-positive. Overall, the SPNM group had a significantly higher mortality rate than the non-SPNM group.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Therefore, we could not individually evaluate the characteristics of anti-ARS antibodies, although anti-PL-7 and anti-PL-12 antibody positivity has been reported to be associated with severe ILD. 22 In summary, SPNM occurred more frequently in anti-MDA5 antibody-positive DM/PM patients than in anti-MDA5 antibody-negative DM/PM patients, and twothirds of the SPNM group were anti-MDA5 antibody-positive. Overall, the SPNM group had a significantly higher mortality rate than the non-SPNM group.…”
Section: Discussionmentioning
confidence: 80%
“…Therefore, we could not individually evaluate the characteristics of anti-ARS antibodies, although anti-PL-7 and anti-PL-12 antibody positivity has been reported to be associated with severe ILD. 22 …”
Section: Discussionmentioning
confidence: 99%
“…The results suggested that activated CD4 + T cell, effector memory CD4 + T cell, memory B cell and type 2 T helper cell may participate in the high TARS expression related immune response in endometrial cancer. Autoantibodies directed against one or more ARSs are present in anti-synthetase syndrome (ASSD), an autoimmune illness that is also defined by clinical symptoms [ 35 ]. Zhou et al reported the tumor mutation burden and immune infiltrates in endometrial cancer [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the genetic disorders of the aaRSs, there is also an acquired autoimmune condition affecting aaRSs, called Anti-Synthetase Syndrome (ASSD). ASSD is a rare condition that involves the production of autoantibodies that bind with, and mount a response against, aaRS proteins ( Kron and Härtlein, 2013 ; Galindo-Feria et al, 2022 ). ASSD is an idiopathic inflammatory myopathy with organ complications beyond the muscles, including interstitial lung disease ( Mahler et al, 2014 ).…”
Section: Anti-synthetase Syndromementioning
confidence: 99%
“…The formal diagnostic criteria for ASSD are based on the presence of anti-aminoacyl tRNA synthetase antibodies along with major (interstitial lung disease and/or polymyositis or dermatomyositis) and minor (arthritis, Raynaud’s phenomenon, mechanic’s hands) criteria ( Solomon et al, 2011 ; Witt et al, 2016 ). The most commonly recognized autoantigen is HisRS (recognized by anti-Jo-1 autoantibodies), but to date, autoantibodies targeting eight aaRSs (HisRS, ThrRS, AlaRS, GlyRS, IleRS, AsnRS, PheRS, TyrRS) have been linked to ASSD ( Ascherman, 2015 ; Galindo-Feria et al, 2022 ). A combination of immunosuppressive agents is used to treat ASSD ( Witt et al, 2016 ).…”
Section: Anti-synthetase Syndromementioning
confidence: 99%